Critical Issues in ELT- Thematic Issue - Salas, Araceli (Ñemitỹrã, 2024)
Welcome to this Thematic Number of our Ñemityra Journal on Critical Issues in English Language Teaching (ELT). In this edition, we explore topics that go beyond the teaching, learning or proficiency of the language and have an impact on the development of students or teachers in ELT. Not everybody likes changes or innovation, however, change is a constant element in all aspects of human life. Language teaching and learning have also changed and evolved, now teachers and students get involved in a more globalized world. This fact makes them realize of other realities and they can engage in dialogues that can open up their personal and professional perspectives. Innovation is the way educators engage in creating new ways to do what they have doing but adapting these actions to new situations and new contexts. In these new contexts is that Critical Issues emerge in ELT. According to Kubota (2020), criticality engages with several aspects related to culture, gender, identity, and intercultural skills. The incursion of criticality in ELT, for some decades now, has had an effect on the efforts that scholars around the world have made in order to raise awareness on issues that still try to maintain certain ideologies as the dominant ones in our field. (Canagarajah, 2020). Some of these topics are reflected in this Thematic Issue of Ñemityra.